Board Interlocking and Firm Performance: Evidence from Indonesia - Pertiwi, Meilinda Brielyan; Yulianto, Arief (Universitas Negeri Semarang, 2020)
This study aims to determine the relationships of board interlocking and firm performance as measured by Return on Assets (ROA). This research method uses a quantitative approach with research objects of all companies listed on the Indonesia Stock Exchange period 2008-2017. The sample selection method uses a purposive sampling. The sample used was 4450 observation. Data analysis methods used are descriptive analysis and dummy variable regression Analysis of Covariance (ANCOVA). The result showed that the average performance of companies that do interlock of directors at other companies at the same time is higher than companies that do not do interlock. The existence of a director who has do interlock allows directors to get access in other places and can mutually utilize resource supported by empirical result where the total assets of companies that do interlock higher than companies that did not interlock. Although concurrent positions can improve the company, the company still complies with government regulations so that the company does not get the law and get sanctionse.